Ответ:
Объяснение:
1.1)=-ху+
2)-2+
3)25-20+4
4)4+28+49
5)-
6)-
2.116+29
3.х^2+8х+16-2х^2=11-(x^2-4x+4)
-х^2+8x+16=7-x^2+4x
8x+16=7+4x
8x-4x=7-16
4x=-9
x=-
4.
m^12-6m^9+8m^6+6m^3-9
подставим m=2,следовательно =1575
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
1.1)=
-ху+![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
![y^{2} y^{2}](https://tex.z-dn.net/?f=y%5E%7B2%7D)
2)
-2
+![a^{6} a^{6}](https://tex.z-dn.net/?f=a%5E%7B6%7D)
3)25
-20
+4![x^{2} x^{2}](https://tex.z-dn.net/?f=x%5E%7B2%7D)
4)4
+28
+49
5)-
6)-
2.116
+29![y^{2} y^{2}](https://tex.z-dn.net/?f=y%5E%7B2%7D)
3.х^2+8х+16-2х^2=11-(x^2-4x+4)
-х^2+8x+16=7-x^2+4x
8x+16=7+4x
8x-4x=7-16
4x=-9
x=-![\frac{9}{4} \frac{9}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%7D)
4.
m^12-6m^9+8m^6+6m^3-9
подставим m=2,следовательно =1575